Humanity-Centered Design in Sustainable Product Design: Literature Review - Geubrina Hikmah Sabri; Rosnani Ginting; Humala Napitupulu (Jurnal Sistem Teknik Industri, 2025)
Product design has emerged as a crucial element in developing innovative solutions that prioritize not only functionality and aesthetics but also sustainability. The Human-Centered Design (HCD) approach has long been employed to ensure that user needs remain the primary focus throughout the design process. However, global challenges such as climate change, social inequality, and the long-term impacts of products necessitate a more comprehensive approach. Consequently, the concept of Humanity-Centered Design has been developed as an extension of HCD, emphasizing the importance of considering the entire ecosystem, other living beings, and long-term consequences in the product design process. This research utilizes a narrative literature review method to examine the Humanity-Centered Design (HuCD) approach within the context of sustainable product design. The review findings indicate that Humanity-Centered Design introduces five key principles, which include a focus on fundamental issues, a holistic ecosystem perspective, long-term outlook, continuous iteration, and community participation. This approach has been shown to enhance the relevance, acceptance, and sustainability of solutions across various sectors, including health technology, manufacturing, and digital domains.